GAMBARAN PERSEPSI ORANGTUA TENTANG PENDIDIKAN SEKSUAL PADA REMAJA TUNAGRAHITA - Warista, Ririn; Dewi, Ari Pristiana; Hairani Damanik, Siti Rahmalia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The parents mostly make formal education as the priority one and they thought sexual education was very negative influence and it is really difficult to deliver that sexual education to mentally retarded adolescents. Meanwhile, for those mentally retarded adolescents in the future will get less information regarding sexual education for their sexual development. Therefore, the perception of sexual education whether it was appropriate or inappropriate it is depending on how people can explain and describe sexual education itself well. The purpose of this study is to describe the perception of parents about sexual education to mentally retarded adolescents in SLB Negeri Pembina Pekanbaru. This research is descriptive quantitative method. Sampling is total sampling with 55 parents. The results of this study showed the parents with the goal of sexual education with positive perception category as many as 30 people (54,55%) and negative as many as 25 people (45,5%), factors causing sexual problems with positive perception counted 31 people (56,45%) and negative as many as 24 people (43.65%); material in giving sexual education with positive perception counted 32 people (58,2%) and negative perception counted 23 people (41,8%); and the way of parents in giving sexual education with positive perception counted 39 people (70,9%) and negative perception counted 16 person (29,1%). The advice given is that parents should further improve the knowledge about sexual education in mentally retarded adolescents especially on the purpose of sexual education so that parents can explain about sexual education appropriately. Keywords: Mentally retarded adolescents, Perception, Sex education